Coronary changes and cardiac events in children diagnosed with kawasaki disease without initial coronary aneurysm: A multicenter retrospective cohort study - Wongbundit, Chanikarn; Vijarnsorn, Chodchanok; Pornprasertchai, Varisara; Somkittitham, Pimonrat; Bositthipichet, Densiri; Tongbunnum, Tikamporn; Chanthong, Prakul (Frontiers in Pediatrics, 2023)
Background: Kawasaki disease (KD) is a systemic vasculitis affecting young children, which may lead to coronary artery aneurysm (CAA). The optimal timing of serial echocardiography in patients with uncomplicated KD is debated. Objectives: To assess changes in coronary artery Z-scores from the initial diagnosis, two weeks, eight weeks, and one year following diagnosis and adverse cardiac events in children diagnosed with KD without initial CAA. Methods: Retrospective chart reviews of four referral centers in Thailand were conducted of all children who were diagnosed with KD without initial CAA (coronary artery Z-score < 2.5) between 2017 and 2020. Eligibility criteria included the absence of congenital heart disease and patients with available echocardiographic evaluations at baseline and at eight weeks of illness. The two-week and one-year echocardiographies were reported. Adverse cardiac events at one year from diagnosis were explored. The primary outcome was a maximal coronary Z-score on the follow-up echocardiography at eight weeks and one year. Results: Of 200 patients diagnosed with KD, 144 patients (72%) did not have CAA. A total of 110 patients were included in the study. The median age was 23 months (IQR, 2-39 months) and 60% were male. Fifty patients (45.5%) had incomplete KD, and four (3.6%) received a second intravenous immunoglobulin treatment. Of 110 patients, 26 patients (23.6%) had coronary ectasia (Z-score of 2-2.49) on their initial echocardiographic examination. Sixty-four patients were evaluated in two-week echocardiographic studies, which showed four new small CAAs and five coronary ectasia. At 8 weeks, 110 patients had undergone complete echocardiographic studies. No patient had residual CAAs. Only one patient had persistent coronary ectasia that regressed to normal within one year. At one-year follow-up (n=90), no cardiac events were reported. Conclusion: New CAA in-patients with KD who had no previous CAA in their initial echocardiography are rare. In addition, patients who had normal echocardiographic follow-up at two weeks or eight weeks mostly continued to be normal at one year. The optimal timing of the echocardiographic follow-up should be at two to eight weeks in patients without initial CAA, who still have a coronary Z-score < 2 at the second echocardiography.